PERENDAMAN BURAYAK IKAN CUPANG (Betta sp.) MENGGUNAKAN MADU TIKUNG UNTUK MENINGKATKAN PERSENTASE JUMLAH JANTAN - Anggoro, Aldio Purbo; Rudi, Mad; Prasetiyo, Himawan; Rouf, Ahmad Beni (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2024)
Male betta fish (Betta sp.) have a high commercial value due to their superior aesthetic qualities compared to females. Sex reversal applications to produce male populations would provide higher profits for ornamental fish breeders. Synthetic steroid hormones are commonly used for sex reversal to induce masculinization. However, synthetic hormones have been banned in aquaculture due to their negative environmental impacts. Therefore, alternative natural and environmentally friendly substances, such as honey, are needed. This study aimed to immerse betta fish fry (Betta sp.) in tikung honey to enhance the percentage of males. The research was conducted experimentally using a completely randomized design with five treatments (P0, P1, P2, P3, P4) and three replications each. The experiment involved immersing 5-day-old betta fry in tualang honey at predetermined doses for each treatment. Treatment P0 served as the control group without honey immersion, while treatments P1, P2, P3, and P4 involved tikung honey immersion at doses of 5, 7, 9, and 11 ml/L, respectively. The results showed that the immersion of betta fry in tikung honey significantly influenced the increase in the percentage of males (P<0,05). The post hoc LSD test revealed a significant difference (P<0,05) between the control group (P0) and all other treatments (P1, P2, P3, and P4). The highest percentage of males was observed in treatment P2 (67.88±10.65%). Based on the findings of this study, the immersion of betta fish fry in tikung honey can effectively increase the percentage of males.